A san remoi megállapodás századik évfordulójára: A modern zsidó állam nemzetközi jogi alapjairól - Mészáros, István László (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2020)
The international law foundations of the modern Jewish State date back to the Resolution of the San Remo Peace Conference in 1920. This Conference transformed the aspiration of reconstituting the Jewish national home in its ancestral territory Palestine into a binding international agreement, setting the stage for the posterior League of Nations Mandate for Palestine in 1922. The Mandate as a legally binding international treaty based on the now hundred years old Resolution assigned the whole land from the line of the River Jordan to the Mediterranean Sea for the Jewish national home. Thus, it is not all the same, whether the international law foundations of the modern Jewish statehood are derived from only the United Nations General Assembly’s “Partition Plan” of 1947 or former international law agreements. This study aims to outline the consequences of the San Remo agreement in the past century.